Neglect, educational success, and young people in out-of-home care: Cross-sectional and longitudinal analyses - Tessier, N; O'Higgins, A; Flynn, R (Elsevier, 2017)
Maltreated young persons in out-of-home care often have poor educational outcomes, heightening their risk of long-term psychosocial disadvantage (Forsman, Brännström, Vinnerljung, & Hjern, 2016). In their systematic reviews, Romano, Babchishin, Marquis, and Fréchette (2014) and O’Higgins, Sebba, and Gardner (in press) found evidence that neglect was more often linked with low academic achievement, whereas abuse was more likely to be associated with behavioral difficulties. In large samples of young persons in out-of-home care in Ontario, Canada, who had experienced mainly neglect, we investigated risk and protective factors as predictors of educational success. In a cross-sectional hierarchical regression analysis (N = 3659, aged 11–17 years), female gender, youth educational aspirations, caregiver educational aspirations for youth, time with current caregiver, internal developmental assets, and positive mental health were associated with better educational success. Neglect, grade retention, special educational needs, ethnic minority status, behavioral problems, and soft-drug use were associated with poorer educational outcomes. Gender significantly moderated caregiver educational aspirations and youth placement type. In a longitudinal analysis of a subsample (N = 962, aged 11–15 years at Time 1), covering three years, a large decline in educational success (d = −0.80) was observed. Female gender, internal developmental assets, and positive mental health positively predicted, and soft drug use negatively predicted, greater educational success at Time 2. These results point to factors that help or hinder educational success among young people in care and should inform new interventions or improved versions of existing ones that address educational success in the context of neglect.